2013
DOI: 10.1186/1471-2296-14-65
|View full text |Cite
|
Sign up to set email alerts
|

Context factors in general practitioner - patient encounters and their impact on assessing communication skills - an exploratory study

Abstract: BackgroundAssessment of medical communication performance usually focuses on rating generically applicable, well-defined communication skills. However, in daily practice, communication is determined by (specific) context factors, such as acquaintance with the patient, or the presented problem. Merely valuing the presence of generic skills may not do justice to the doctor’s proficiency.Our aim was to perform an exploratory study on how assessment of general practitioner (GP) communication performance changes if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…Thus, GPs seemed to tailor their reassurance to the context of that specific consultation, which explains why they described such a wide variety of strategies. The context-specific and goal-directed character of doctor-patient communication has also been shown in previous research [27,40,41]. The situation-specificity of reassurance has also been demonstrated in our study exploring the patients’ perspective on reassurance, which showed that what is experienced as reassuring by patients largely depends on their specific worrying cognitions [38].…”
Section: Discussionsupporting
confidence: 84%
“…Thus, GPs seemed to tailor their reassurance to the context of that specific consultation, which explains why they described such a wide variety of strategies. The context-specific and goal-directed character of doctor-patient communication has also been shown in previous research [27,40,41]. The situation-specificity of reassurance has also been demonstrated in our study exploring the patients’ perspective on reassurance, which showed that what is experienced as reassuring by patients largely depends on their specific worrying cognitions [38].…”
Section: Discussionsupporting
confidence: 84%
“…Trainees' reflections on situations during which the skills they have learned during medical training are ineffective, again underline that the context-specific nature of medical communication in daily practice should not be ignored [27][28][29][30]. In line with previous studies, there seems to be a need for more tailored, context-specific communication strategies that are adaptable to specific situations [31,32].…”
Section: Main Findings In Relation To the Literaturementioning
confidence: 56%
“…This instrument is being used, in real-time and in recorded sessions, to assess students, physicians and/or nurses at only a small number of institutions in different countries. However, it is important to recognize that it is not being more widely adopted as a gold standard [73][74][75]. It is apparent from this review that the majority of CS assessment is based upon the individual development of unique measurement instruments which are used only at local level.…”
Section: Discussionmentioning
confidence: 99%